Comparison of the efficiency between electrocardiogram and echocardiogram for left ventricular hypertrophy evaluation in patients with hypertension: Insight from the Korean Hypertension Cohort Study. Issue 11 (21st October 2022) - Park, Bo Eun; Lee, Jang Hoon; Jang, Se Yong; Lee, Hae‐Young; Lee, Ju‐Yeon; Shin, Ho‐Gyun; Park, Kyun‐Ik; Lee, Seung‐Pyo; Lee, Hee‐Sun; Kim, Kwang‐Il; Kang, Si‐Hyuck; Lee, Ju‐Hee; et al.
Abstract: In patients with hypertension, left ventricular hypertrophy (LVH) represents a risk factor for cardiovascular disease and asymptomatic organ damage. Currently, electrocardiography (ECG) and two‐dimensional echocardiography (Echo) are the most widely used methods for LVH evaluation. This study aimed to compare the long‐term outcomes of LVH, as evaluated by ECG and Echo, in patients with hypertension. Patients diagnosed with hypertension as a primary disease between 2006 and 2011 were enrolled in the Korean Hypertension Cohort study. The study finally included 1743 patients who underwent both ECG and Echo. The primary endpoint was defined as the composite of major adverse cardiovascular events (MACEs) or death. Overall, LVH was identified in 747 patients. The patients were categorized into four groups according to the detection of LVH by ECG or Echo: No LVH (n = 996), LVH diagnosed by ECG alone (n = 181), LVH diagnosed by Echo alone (n = 415), LVH diagnosed by both ECG and Echo (n = 151). After adjusting for variables, the incidence of MACEs or death was significantly greater in patients with LVH diagnosed by ECG alone (hazards ratio [HR]: 1.69; 95% confidence interval [CI]: 1.22–2.35; P  = .001), LVH diagnosed by Echo alone (HR: 1.54; 95% CI: 1.16–2.05; P  = .002), and LVH diagnosed by both ECG and Echo (HR: 1.87; 95% CI: 1.18–2.94; P  = .002) than in those with no LVH. Both ECG and Echo are efficient diagnostic tools for LVH and useful for long‐term risk stratification. Additional Echo evaluation for LVH is helpful for predicting long‐term outcomes only in patients without LVH diagnosis by ECG.